Про використання моделей пульсацiй тиску на плоскiй стiнцi для опису пульсацiй тиску на поверхнях цилiндричних конструкцiй. Аналiз результатiв - Борисюк, А.О. (Видавничий дім "Академперіодика" НАН України, 2008)
Conditions are searched, at which the available pressure fluctuation models on a flat wall (i. e., the models of Corcos, Chase, F. Williams, and Smol’yakov and Tkachenko) can be used to describe the pressure fluctuation field at surfaces of cylindrical structures on their interaction with fully developed turbulent flows of an incompressible fluid. For this purpose, an appropriate method and an experimental equipment are developed. As a result, it is found that, in case of axial symmetry of the flow, the acceptable-for-practice results of calculations of the vibration and/or acoustic fields of cylindrical structures can be obtained in the frames of the Chase model. This allows one to recommend the use of the model to describe the pressure field noted above. In case of a non-axisymmetric flow, the application of all the pressure fluctuation models on a flat wall is unreasonable.